Over‐Representation of TTN Truncating Variants in a Finnish Cohort of Patients With Axial Myopathy - Di Feo; Maria Francesca; Capece, Giuliana; Savarese, Marco; Udd, Bjarne; Jokela, Manu; Palmio, Johanna (Wiley, 2026)
Background
Axial myopathies present with late onset selective paravertebral weakness causing bent spine/camptocormia or dropped head, and the genetic basis remains currently only partially understood. Truncating variants in TTN (TTNtv) are found in about 1% of the general population and, when biallelic, cause recessive titinopathies. Also, TTNtv located in cardiac exons are known to confer an increased risk of cardiomyopathy, with incomplete penetrance.
Methods
We retrospectively analyzed 55 Finnish adults with late-onset axial myopathy evaluated at the Tampere Neuromuscular Center (2015–2025). Clinical, imaging, and histopathological data were collected, and genetic testing was performed using the MYOcap targeted next-generation sequencing panel.
Results
Heterozygous TTNtv were identified in 9 of 55 patients (16%), representing a significant enrichment compared with the general population (odds ratio = 14.1; p ≈5 × 10−8). The variants were ultra-rare, distributed across different exons expressed in skeletal muscle, and five were absent from gnomAD. Mean age at onset was 60 ± 11 years; six patients were female, and five reported a positive family history. Camptocormia was the main presentation, with muscle MRI showing a consistent fatty-fibrous replacement of paravertebral muscles in all cases. Muscle biopsies revealed either myopathic or myofibrillar changes without a uniform pattern.
Conclusions
Heterozygous TTNtv are significantly enriched in patients with late-onset axial myopathy, suggesting a potential contribution to this phenotype. These findings broaden the clinical spectrum of titin-related diseases and support inclusion of TTN in genetic testing for idiopathic axial myopathies.